2019
DOI: 10.1111/bcp.13940
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous antazoline, a first‐generation antihistaminic drug with antiarrhythmic properties, is a suitable agent for pharmacological cardioversion of atrial fibrillation induced during pulmonary vein isolation due to the lack of influence on atrio‐venous conduction and high clinical effectiveness (AntaEP Study)

Abstract: Aims: Antazoline is a first-generation antihistaminic drug used primarily in eye drop formulations. When administered intravenously, antazoline displays antiarrhythmic properties resulting in a rapid conversion of recent-onset atrial fibrillation (AF) to sinus rhythm (SR).The aim of the study was to assess the influence of antazoline on atrio-venous conduction and other electrophysiological parameters in patients undergoing AF ablation.Methods: An experimental prospective study. Patients scheduled for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It is noteworthy that our search retrieved a total of 6 articles (in 1612 patients) that included PCV using antazoline mesilate. 19,[32][33][34]42,66 This is an old antihistaminic drug, which, despite its proven antiarrhythmic efficacy, is not currently mentioned in any AF guidelines. [72][73][74] According to publicly available data, it appears that the intravenous form of antazoline is registered and sold in Poland only; therefore, it is not surprising that majority of the research on antazoline was conducted and published by Polish physicians.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that our search retrieved a total of 6 articles (in 1612 patients) that included PCV using antazoline mesilate. 19,[32][33][34]42,66 This is an old antihistaminic drug, which, despite its proven antiarrhythmic efficacy, is not currently mentioned in any AF guidelines. [72][73][74] According to publicly available data, it appears that the intravenous form of antazoline is registered and sold in Poland only; therefore, it is not surprising that majority of the research on antazoline was conducted and published by Polish physicians.…”
Section: Resultsmentioning
confidence: 99%
“…Antazoline is an anti-histaminic drug that has also been repurposed for AF management due to its multi-ionic effects and has shown effectiveness in AF cardioversion during PVI [ 151 , 152 ]. In addition, a small RCT of 74 paroxysmal AF subjects (AnPAF study) demonstrated that intravenous antazoline is effective in rapid cardioversion of AF [ 153 ].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Cryoablation is primarily used to treat paroxysmal AF when the sources of the arrhythmia are focally located in the pulmonary vein region of the left atrium (LA) [ 7 ]; however, it is also proven to be safe and effective treatment of persistent AF, which is accompanied by complex underlying mechanisms such as progressive electrical, structural remodeling and fibrosis of the atrial myocardium [ 8 ]. The pulmonary vein isolation (PVI) procedure may induce AF, and hence affect its assessment; therefore it generally requires subsequent electrical or pharmacological cardioversion [ 9 ]. Transthoracic synchronized CVE is well known as the treatment of choice in immediate termination of AF and restoring sinus rhythm among hemodynamically unstable patients and it is more effective than pharmacological cardioversion despite the requirement of sedation.…”
Section: Introductionmentioning
confidence: 99%